Apropriação de ambientes físicos de serviços por tribos urbanas: o caso Casa da Matriz - Halpern, Eduardo Espíndola (2008)
The research´s main goal was to understand how certain servicescapes are apropriated by groups of individuals who use them to build its cultural identidy, changing its original economic purpose. The literature review conducted to give theorical support to the investigation was based on services marketing and, more specificaly, on servicescapes. The field research was conducted in Casa da Matriz, a night club located in the neighborhood of Botafogo in the south side of the city of Rio de Janeiro. In depht interviews and participant observation were used to identify the approach used to design and to manage the servicescape of Casa da Matriz and the appropriation practices used by its customers in order to build theis cultural identidy.